Assistive technology interfaces for the blind - Calder, David (IEEE, 2009)
Assistive technology devices for the blind are portable electronic devices that are either hand-held or wornby the visually impaired user, to warn of obstacles ahead. Many assistive technology devices use ultrasonic pulse-echo techniques to gauge subject to object distance. Some use infrared light transceivers or laser technology to locate and warn of obstacles. These devices exhibit a number of problems, the most significant of which are related to the interface display that conveys navigation/obstacle warning information to the user. Other sensory channels should not be compromised by the device. This is exactly what can happen when, for example, audio signals are used in obstacle warning on/off displays or more significantly in orientation solutions, where continuous streams of synthetically generated stereo sound mask the natural ambient sound cues used by the blind. Despite the challenges, the commendable feature all these assistive device developers have in common is; they are striving to help a section of the population with a severe disability. Even if there is only partial success in this endevour to assist the blind, the small companies that produce these devices all have the right motive. That is a big step in the right direction. The author has attempted to address some of the problems mentioned in this paper by producing a first working prototype. Improvements to this original design form the basis for ongoing prototype development within the DEBI Institute at Curtin University.